Truth or scare UFOs over Phoenix - Calderone, Fran; Rapsas, Jim; Drachkovitch, Rasha; Drachkovitch, Rasha (MagnaVision Incorporated, 2005)
Are UFO's Truth or Scare? Strange lights or objects in the night sky over central Arizona, reported by hundreds of people on March 13, 1997, made national news and added to the on-going lore of UFO sightings. Hosted by Michelle Trachtenberg, Truth or Scare examines just what happened that night and the theories that explain it. Home videos, eyewitnesses and experts portray the happening while skeptics who feel that the Phoenix lights have a conventional explanation tell why.